2006
DOI: 10.4103/0019-5545.31555
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of standardized Bacopa monniera extract in age-associated memory impairment

Abstract: Background:Brahmi (Bacopa monniera) is a traditional Indian medicinal plant which causes multiple effects on the central nervous system. The standardized extract of this plant has shown enhanced behavioural learning in preclinical studies and enhanced information processing in healthy volunteers.Aim:To study the efficacy of standardized Bacopa monniera extract (SBME) in subjects with age-associated memory impairment (AAMI) without any evidence of dementia or psychiatric disorder.Methods:A double-blind, placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 8 publications
0
59
0
Order By: Relevance
“…Diseases can be prevented by following a proper daily routine and seasonal living. The rich repository of unique efficacious plants mentioned in Āyurveda has elicited a significant hope in current drug discovery research, which is characterized by a target-rich and lead-poor scenario [55,56]. Increased interest is being witnessed at a global scale to evolve drug discovery strategies based on natural products and traditional medicine, and it is being increasingly realized that development of new drugs need not always be restricted to new molecular entities [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diseases can be prevented by following a proper daily routine and seasonal living. The rich repository of unique efficacious plants mentioned in Āyurveda has elicited a significant hope in current drug discovery research, which is characterized by a target-rich and lead-poor scenario [55,56]. Increased interest is being witnessed at a global scale to evolve drug discovery strategies based on natural products and traditional medicine, and it is being increasingly realized that development of new drugs need not always be restricted to new molecular entities [57].…”
Section: Discussionmentioning
confidence: 99%
“…No abnormalities were observed in genotoxicity and mutagenicity [52]. The product was efficacious in the treatment of children suffering from attention deficit hyperactive disorder [53] and adults suffering from age-associated memory impairment [54,55,56] (Figure 13, Figure 14). …”
Section: Medhya-rasayana (Memory Enhancing and Rejuvenating) Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been demonstrated that consumption of B. monnieri at a dose of 300 mg per day can enhance logical memory, paired associated learning, and mental control in age-associated memory impairment (AAMI) subjects without serious adverse effects. However, “flu-like symptoms” and “digestive problems” were also observed [16]. A systematic review of studies also shows that consumption of B. monnieri at doses of 300–450 mg/day can enhance memory recall [17–22].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action purported to be responsible for these cognitive enhancements is linked to the mitigation and protection of neuronal cholinergic systems following administration of B.monnieri [ 9 , 12 , 13 ]. Recent innovative research reported significant improvements in memory in healthy older adults [ 14 ], as well as in a population of older adults with age-associated memory impairment [ 15 ] following administration with B.monnieri. These findings show promise for ageing research, with cholinergic degeneration a major clinical feature of both age-related cognitive decline and Alzheimer’s dementia [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%